Essence Of Integration And Methodology Of Its Study In Elementary Mathematics Education (Journal of Pedagogical Inventions and Practices, 2025)
The concept of integration in elementary mathematics education is pivotal, serving as a foundation for more complex mathematical thinking and problem-solving. This article delves into the essence of integration, exploring its theoretical underpinning and methodological significance. By examining its role in mathematics pedagogy, we propose a structured approach to enhancing students' understanding and application of integration, drawing on prior research and contemporary educational practices